HOW TO DISTINGUISH NATURALLY FRACTURED RESERVOIRS FROM STRATIFIED RESERVOIR SYSTEMS IN A WELL TEST ANALYSIS - Wahyu Jatmiko (Testing Center for Oil and Gas LEMIGAS, 1994)
In the real well test analysis, to identify an exact reservoir model in heterogeneous reservoirs is very difficult. The geological model will guide the direction of the well test interpretations. For the similar reservoir condition, a different reservoir model.